Female sexuality : new psychoanalytic views - Chasseguet-Smirgel, Janine, 1928-2006 (Karnac, 1992)
Contains six essays and an introduction on Freudian and non-Freudian views of female sexuality. Contributors include Joyce McDougall, Maria Torok and Bela Grunberger.
Keywords: Women -- Psychology.; Psychoanalysis.; Women -- Sexual behavior.; Femmes -- Psychologie.; Psychanalyse.; Femmes -- Sexualité.; psychoanalysis.; PSYCHOLOGY -- Human Sexuality.; Psychoanalysis; Women -- Psychology; Women -- Sexual behavior